Preparing Preservice EFL Teachers to Conduct Classroom Research to Overcome Demotivation: A Conceptual Study - Adara, Reza Anggriyashati (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Demotivation has an adverse affect toward students’ interests in EFL (English as foreign language) learning. In this regard, teachers can be a key factor that helps students overcome students’ demotivation. Therefore, it seems important for EFL preservice teachers to be trained on how to conduct a classroom research to identify demotivation factors and overcome demotivation among their future students. The present study is a conceptual study that aims to propose the importance of training preservice teachers to perform classroom research in order to diagnose and eliminate demotivation among their future students. Thus, the present study proposes three steps to train preservice teachers. First, preservice teachers will be given a case study about students’ demotivation to be analyzed to find the solutions. Second, a focus group discussion with inservice teachers will be conducted to discuss the latter’ strategies to reduce demotivation. Third, preservice teachers will be trained with various motivational strategies that can be adapted according to their future students’ needs. The present study aims to equip preservice teachers with adequate knowledge toward their future students as well as a better classroom management in order to reduce demotivation.